Adsorption of Cd and Cr ions from industrial wastewater using Ca doped Ni–Zn nanoferrites: Synthesis, characterization and isotherm analysis. Issue 13 (1st July 2022) - Punia, Pinki; Aggarwal, R.K.; Kumar, Rakesh; Dhar, Rakesh; Thakur, Preeti; Thakur, Atul
Abstract: Removal of heavy metals (Cd and Cr) from industrial wastewater by adsorption onto a series of Ca substituted nickel zinc nanoferrites (Cax Ni0.4 Zn0.6-x Fe2 O4 (x = 0.1, 0.2, 0.3, 0.4, 0.5 and 0.6)) (CNZNFs) was studied in detail. The effect of calcium doping and contact time over adsorption of cadmium and chromium ions was investigated and maximum uptake of Cd (98.25%) and Cr (51%) ions were marked by prepared nanoadsorbents. Structural studies confirmed the formation of spinel structured nanoparticles with crystallite size ranging from 24 to 38 nm while porosity was observed to vary from 52% to 58% with calcium concentration. Pseudo second order (PSO) kinetic model for adsorption of both heavy metals (cadmium and chromium) was observed to be better fitted with adsorption data. Maximum adsorption efficiencies for Cd (128.20 mg/g) and Cr (23.54 mg/g) were found by the data fit of Langmuir isotherm model. Additionally, the adsorption data was found to obey Langmuir isotherm model for both heavy metals due to higher values of correlation coefficients (R 2 = 0.94131 for cadmium and 0.91091 for chromium) than Freundlich isotherm model (R 2 = 0.5865 for cadmium and 0.4599 for chromium). Highlights: Formulae used for calculations of structural parameters from XRD plots Linear and non linear equations for adsorption kinetics and isotherm models Parameters calculated by pseudo first order and pseudo second order adsorption kinetics Results of various plots for adsorption of cadmium and chromium ions onto Cax Ni0.4 Zn0.6-x Fe2 O4 (x = 0.1) magnetic nanoparticles